Long-Division Problems for Elementary Students - Perawati Tri Nanda; Al Jupri (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
The operation of counting numbers is one of the basic mathematical concepts that must be mastered by students. The arithmetic operations consist of addition, subtraction, multiplication and division. The operation of dividing whole numbers is considered difficult to learn and teach. However, it is very important for students because many aspects of mathematics are needed in daily life. In the current situation, it was found that many students had problems learning the concept of long division. This study aims to describe the problems experienced by elementary school students and the factors that cause students difficulties in completing long-division operations. The method used is qualitative by collecting library data. The subjects in this study were articles related to the problems faced by elementary school students in completing long-division operations. Documenting data collection and the use of articles related to students' problems in solving long-division operations. Based on this study, the problems experienced by students were not mastering the concept of multiplication, errors found in counting, not being fluent in using operations or procedures, and not understanding the origin of the long division concept. Factors causing these difficulties are external factors that come from the teacher and the environment. While the internal factors come from the students themselves.